Pembinaan Misdinar Untuk Meningkatkan Kesiapan Pelayanan Altar di Paroki Spiritu Santo Misir - Veronika Delvriana; Hermania Bhoki (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The Community Service Program (KKN) focusing on altar server (misdinar) formation at the Holy Spirit Misir Parish was carried out to respond to the need for improving the readiness of altar service in liturgical celebrations. This topic was chosen because altar servers have an important role in supporting the smooth implementation of the Eucharist, which requires understanding of liturgical order, disciplined behavior, and technical skills. The method used included field observation, coordination with liturgical officers, preparation of training modules, and implementation of training sessions consisting of theoretical explanations, task demonstrations, and direct altar practice. Periodic evaluations and participant feedback were also conducted to assess the effectiveness of the training materials. From the results, it was observed that there was an increase in the altar servers’ understanding about liturgical rubrics, accuracy of movements, readiness of liturgical items, and teamwork abilities. In this case, participants showed more positive attitudes, stronger discipline, and increased confidence when serving. Moreover, structured training helped establish a more or ganized workflow, contributing to smoother and more orderly liturgical celebrations. These findings show that targeted and continuous formation can very much improve the quality of altar service. Thus, this KKN program provides meaningful contributions to strengthen the competence of misdinar and can be made into a model for similar training programs in other parishes that want to improve the quality of liturgical service.